P13 Role of one-step nucleic acid amplification (OSNA) to detect sentinel lymph node micro-metastasis in early-stage cervical cancer. (1st November 2019) - Bizzarri, N; Pedone Anchora, L; Zannoni, GF; Santoro, A; Valente, M; Gallotta, V; Conte, C; Teodorico, E; Di Fiore, GLM; Ghirardi, V; Fagotti, A; Ferrandina, G; et al.
Abstract : Introduction/Background: Evidence in literature supports the accuracy of sentinel lymph node (SLN) in early-stage cervical cancer. SLN is usually analyzed through ultra-staging examination, which cannot be performed intraoperatively as it is too cumbersome and time-consuming. One-step nucleic acid amplification (OSNA) is a rapid assay able to detect cytokeratin (CK)19-mRNA in SLN and it can be used for intra-operative detection of macro-metastasis, micro-metastasis and isolated tumor cells (ITC). It consists of a short homogenization step followed by amplification of CK19-mRNA directly from the lysate. We aim to evaluate if OSNA could be used to detect micro-metastasis in patients with early cervical cancer. Methodology: Consecutive patients who underwent surgery for FIGO stage IA1 LVSI+ to IB1 between 01/2015-02/2019, and had SLN biopsy±pelvic lymphadenectomy (PLN), were included. SLN was detected with cervical injection of indocyanine-green (1.25 mg/ml) and sent intra-operatively for OSNA. OSNA result was considered: negative: <160 CK19-copies/µL; ITC 160-249 CK19-copies/µL; micro-metastasis 250-5000 CK19-copies/µL; macro-metastasis >5000 CK19-copies/µL. The first 12 OSNA cases had immunohistochemistry staining for CK19 in the primary tumour. Results: 109 patients underwent SLN biopsy: 59 (54.1%) were analyzed with H&E, 29 (26.6%) with OSNA and 21 (19.3%) with ultra-staging. 12/12 (100%) primary tumors were CK19-positive. Patients' characteristics are demonstrated in table 1. In the OSNA group, 5 (17.2%) patients had unilateral and 24 (82.8%) bilateral mapping. OSNA detected micro-metastasis in 7/29 (24.1%) patients. In 5/7 (71.4%) cases, systematic bilateral PLN was performed and in all these patients, SLN was the only positive node. When PLN was performed, no false negative in bilateral detection and 1/5 (20%) false negative with unilateral detection was found. Conclusion: This is one of the first series investigating the application of SLN CK19-OSNA in early-cervical cancer. OSNA is able to detect micro-metastasis in SLN. However, further cases are necessary to define the positive predictive value of this technique. Disclosure: Nothing to disclose.